Vivência com o portador de transtorno mental : perspectivas de familiares usuários da atenção básica - Estevam, Michelle Caroline (2009)
The current national policy on mental health is based on desinstitutionalization aiming at replacing the care given to mental patients in closed institutions for areas outside hospitals, emphasizing the maintenance of social and family bonds. Within this context there is an obvious burden on the family by having to take an active role in the treatment of its family member. Therefore, professionals need to provide these families with an appropriate and healthy living. Thus, the Family Health Strategy is suitable for working with mental health in primary care, since this team is involved in the community's day-to-day and can take actions to promote education and improve their living conditions. Understanding the main problems and the potentials that are emerging in the context of primary care on mental health is fundamental for health professionals committed to ethical and complete care. This study aimed at: understanding the daily lives of families of mentally ill users of primary care in Maringá-PR and identifying the assistance offered to these families by the Family Health Strategy (FHS) professionals from the family perspective. This is a qualitative study where data were collected from 18 informants from seven families of mentally ill patients, between June and July 2009 in their homes. Data were gathered through a guiding question: Tell me about your life after the diagnosis of mental disorder of your family member associated with other issues necessary to meet the object of study. The data were analyzed according to Bardin, which generated three broad categories: 1) Experiences of relatives with a mental disorder member: life after diagnosis, 2) relations and feelings arising from living with a mental disorder member, 3) Caring in primary care: the relatives perspective of mental patients, and five subcategories: 1) feelings aroused when living with mental illness: family accounts, 2) interpersonal relations in face of mental disorder: changes, meanings and perceptions; 3) New ways of acting in the face of mental disorder, 4) Performance of the primary care givers from the family perspective, 5) willingness to care: a family proposal. The families studied showed many difficulties, such as the emerging crisis due to the disease diagnosis, experiencing negative feelings such as guilt, fear, anger, doubt, among others, frustration by the impossibility of healing, relationship difficulties, financial problems, prejudice and stigma which leads to segregation and social isolation and other difficulties, thus, requiring continued, comprehensive and effective assistance from health professionals, especially nursing. However, these family members perceive the health service assistance as unsatisfactory and neffective and the health professionals as not possessing the necessary sensitivity and skill to build relationships and assist them. Therefore, it is important that health professionals review their practices, take updating courses, act in a multidisciplinary and interdisciplinary way, plan their assistance and meet these families into their reality.